2010
DOI: 10.1021/ja908398u
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Changes in Mechanochemically Synthesized Magnesium Hydride Nanoparticles

Abstract: The thermodynamic properties of magnesium hydride nanoparticles have been investigated by hydrogen decomposition pressure measurements using the Sieverts technique. A mechanochemical method was used to synthesize MgH(2) nanoparticles (down to approximately 7 nm in size) embedded in a LiCl salt matrix. In comparison to bulk MgH(2), the mechanochemically produced MgH(2) with the smallest particle size showed a small but measurable decrease in the decomposition reaction enthalpy (DeltaH decrease of 2.84 kJ/mol H(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
239
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(253 citation statements)
references
References 33 publications
9
239
5
Order By: Relevance
“…45 This MgH 2 −TiH 2 nanocomposite exhibits outstanding kinetic properties and cycling stability. 45 Nanocrystals of MgH 2 (∼7 nm in size) embedded in a matrix of LiCl were reported by Paskevicius et al 46 using mechanochemical metathesis reaction between MgCl 2 and LiH. 46 In this study the enthalpy (ΔH) was decreased by 2.84 kJ/mol H 2 , from 74.06 ± 0.42 kJ/mol H 2 for the bulk to 71.22 ± 0.49 kJ/mol H 2 for the 7 nm crystals.…”
Section: Studies On Nanoparticlesmentioning
confidence: 86%
See 1 more Smart Citation
“…45 This MgH 2 −TiH 2 nanocomposite exhibits outstanding kinetic properties and cycling stability. 45 Nanocrystals of MgH 2 (∼7 nm in size) embedded in a matrix of LiCl were reported by Paskevicius et al 46 using mechanochemical metathesis reaction between MgCl 2 and LiH. 46 In this study the enthalpy (ΔH) was decreased by 2.84 kJ/mol H 2 , from 74.06 ± 0.42 kJ/mol H 2 for the bulk to 71.22 ± 0.49 kJ/mol H 2 for the 7 nm crystals.…”
Section: Studies On Nanoparticlesmentioning
confidence: 86%
“…45 Nanocrystals of MgH 2 (∼7 nm in size) embedded in a matrix of LiCl were reported by Paskevicius et al 46 using mechanochemical metathesis reaction between MgCl 2 and LiH. 46 In this study the enthalpy (ΔH) was decreased by 2.84 kJ/mol H 2 , from 74.06 ± 0.42 kJ/mol H 2 for the bulk to 71.22 ± 0.49 kJ/mol H 2 for the 7 nm crystals. The entropy (ΔS) also decreased from 133.4 ± 0.7 J/k mol H 2 to 129.6 ± 0.8 J/k mol H 2 .…”
Section: Studies On Nanoparticlesmentioning
confidence: 86%
“…The ensuing large decomposition enthalpy of 75 kJ mol -1 H 2 results in relatively high desorption temperatures (>300 °C) coupled with a slow hydrogen diffusion rate, limiting its practical applications. 5 Different approaches such as catalysis, 6,7 alloying, 8,9 composite formation 10,11 and nanostructuring [12][13][14] have been employed to improve the hydrogen uptake/release kinetics and thermodynamics of MgH 2 . One of the most widely used strategies is to reduce the MgH 2 particle size by mechanical ball milling, hence lowering the activation energy of desorption.…”
Section: Introductionmentioning
confidence: 99%
“…This may allowp ractical utilisation under more moderatec onditions. Experimental studies have shown that the thermodynamic properties are more favourable for nano particles ($5nm) (Paskevicius, Sheppard and Buckley, 2010) and nanoconfinement have been shown to improvet he reversibility,s tability,k inetics, and possibly also the thermodynamic properties of chemical reactions involved in reversible release and uptake of hydrogen (Nielsen et al,2009;Nielsen et al,2010). Bogdanović and Schwickardi, 1997 showed that NaAlH 4 can reversibles tore hydrogen at more moderate conditions by doping with titanium compounds.…”
Section: Introductionmentioning
confidence: 99%